Quality of life in patients with vitiligo - Bhuptani, Neela V.; Parmar, Pratik J.; Selot, Nilam K.; Patel, Bharti K. (International Journal of Research in Dermatology, 2020)
Background: Vitiligo is an acquired disorder characterized by well circumscribed depigmented macules and patches that result from a progressive loss of functional melanocytes. In India and perhaps elsewhere also patients with vitiligo have severe psychological and social problems. Quality of life is multidimensional index of different social, behavioural and cultural factors. Different tools were developed for measuring quality of life focusing on different conditions and diseases. The dermatology life quality index (DLQI) questionnaire is designed for use in patients of age more than 16. It can be used to measure the impact of vitiligo on quality of life. To assess the dermatology specific quality of life in patients with vitiligo. To study impact of vitiligo on their quality of life. Methods: In this study 150 patients diagnosed with vitiligo during a 1-year period were included. DLQI was calculated for every patient. Results: The mean DLQI score in our study was 6.14. There was a statistically significant difference in mean DLQI of unmarried as compared to married. There were no statically significant differences in other groups. Out of 150 patients of vitiligo, 3 (2%) patients had no effect, 66 (44%) patients had small effect, 69 (46%) patients have moderate effect, while 12 (8%) patient had very large effect of vitiligo on their quality of life. Conclusions: Vitiligo affects quality of life in majority of patients. So, it should be treated aggressively with various treatment modality along with proper counselling and psychological support.